Bioprospecção de espécies de microalgas dulcícolas da região nordeste do Brasil para a produção de biocombustíveis - Pereira, Elizandra Ribeiro de Lima (2019)
Microalgae are unicellular organisms, microscopic and photosynthetic, that can produce significant amounts of metabolites of biotechnological interest. The present study aimed to study regional species of microalgae isolated from the Northeast region of Brazil (Paraíba, Piauí, Rio Grande do Norte and Bahia) as to their capacity to produce lipids and other compounds of biotechnological interest and their development in medium low cost alternative, Among the 10 species studied were identified 5 potentials for the production of biofuel: Scenedesmus quadricauda (D125WC) Coelastrum sp. (D193WC), Pediastrum boryanum (D231WC), Ankistrodesmus falcatus (D245WC) and Selenastrum gracilis (D458WC), with biomass productivity ranging from 104.7 to 165.72 gL-1d-1 and higher ester contents than soybean. The species were cultured under controlled conditions and the culture was monitored by cell counts and by in vivo fluorescence measurements. Growth parameters were monitored and compared between the species and from the obtained biomass were determined proteins, carbohydrates, lipids, profile of fatty acids and antioxidant potential. A mass experiment was carried out in an open tank (canal) with a capacity of 13,000 L, with the species Scenedesmus quadricauda, in an alternative medium (Biocomposto hortifrutis (BH)). Scenedesmus quadricauda (D125WC) microalgae oil, besides characterization by infrared absorption spectroscopy (FTIR). For the thermal and oxidative stability of the extracted fractions, thermogravimetry (TG), Differential Exploration Calorimetry (DSC) and Rancimat were analyzed. Analysis was carried out in the unsaponifiable fraction, identifying the presence of bioactive compounds (Carotenoids) in a large quantity (4050 μg / g), presenting a high antioxidant index, being efficient in the addition of additives in biodiesel, adding 1.25%. The obtained biodiesel does not present viability for its pure use in motors due to its high viscosity and oxidation index not stabilized, however, it presents viability for its insertion in blends of biofuel. The results of this study show that species isolated from the Northeast of Brazil are viable for large-scale production, producing biofuels and other high-value aggregates for the biotechnology industry.